2016
DOI: 10.1016/j.ajpath.2015.11.028
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 Drives Eosinophil Infiltration and Pathogenic Type 2 Helper T-Cell Immune Responses Leading to Chronic Experimental Ileitis

Abstract: Although a clear association has been established between IL-33 and inflammatory bowel disease, mechanistic studies to date, primarily using acute murine models of colitis, have yielded contradicting results, demonstrating both pathogenic and protective roles. We used a well-characterized, spontaneous model of inflammatory bowel disease [ie, SAMP1/YitFc (SAMP) mice] to investigate the role of IL-33 during chronic intestinal inflammation. Our results showed marked eosinophil infiltration into the gut mucosa wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 50 publications
3
71
0
Order By: Relevance
“…Efforts to circumvent metaplasia development through manipulation of EGF ligands/receptors (Areg [34], EGFR [34, 35]), endocrine pathways (gastrin [10, 36], histamine [37]) and cytokines (IFNγ [38, 39, 40], IL–11 [41]) have yet to identify factor(s) necessary for the induction of metaplasia in response to parietal cell loss in either an acute drug induced system or chronic Helicobacter infection. Previous studies found that administration of IL-33 is sufficient to induce hypertrophy and mucous metaplasia in the airway, stomach, and intestine through the induction Th2 cytokines and infiltration of myeloid cells and eosinophils [20, 21, 42, 43, 44, 45]. Furthermore, it is well-established that IL-33 signaling results in up-regulation of the expression of IL-13, which is required for the development of mucous metaplasia in the airway allergic response.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to circumvent metaplasia development through manipulation of EGF ligands/receptors (Areg [34], EGFR [34, 35]), endocrine pathways (gastrin [10, 36], histamine [37]) and cytokines (IFNγ [38, 39, 40], IL–11 [41]) have yet to identify factor(s) necessary for the induction of metaplasia in response to parietal cell loss in either an acute drug induced system or chronic Helicobacter infection. Previous studies found that administration of IL-33 is sufficient to induce hypertrophy and mucous metaplasia in the airway, stomach, and intestine through the induction Th2 cytokines and infiltration of myeloid cells and eosinophils [20, 21, 42, 43, 44, 45]. Furthermore, it is well-established that IL-33 signaling results in up-regulation of the expression of IL-13, which is required for the development of mucous metaplasia in the airway allergic response.…”
Section: Discussionmentioning
confidence: 99%
“…However, Bamias et al 25 showed that germ-free SAMP1/YitFc mice develop ileitis with varying degrees of severity, the majority showing a milder form of the disease, confirming the importance of the gut microbiome as a modulating factor of chronic intestinal inflammation. The absence of a commensal flora appears preferentially to impact the Th2-driven chronic phase of SAMP1/YitFc ileitis, with significantly reduced levels of IL33, and downstream IL5 and IL13 at 13 weeks of age, and decreased chronic inflammatory scores through 30 weeks of age, providing further evidence that interactions with the gut microbiome drive production of Th2 cytokine production during the chronic phase of SAMP1/YitFc ileitis 26, 73…”
Section: Pathogenic Mechanisms Of Crohn’s-like Ileitismentioning
confidence: 97%
“…In DSS-induced chronic colitis, IL-33 ameliorates the intestinal inflammation through suppressing Th1 and Th17 responses [82]. However, in SAMP1/YitFc spontaneous chronic murine colitis model, IL-33 administration worsens the chronic intestinal inflammation by enhancing eosinophil infiltration and increasing pathogenic Th2 response [83]; these effects can be reversed by blockade of IL-33 signaling or depletion of eosinophils and required gut microbiomes [83, 84]. These animal findings indicate that IL-33 may confer protection from injury or lead to inflammation although the behind mechanisms remain largely undefined.…”
Section: Il-1 Familymentioning
confidence: 99%